High Prevalence Of Antibody Response Against Plasmodium Falciparum (Pf) Antigens In A Holoendemic Area Of Benin (1994-1995) - S. Judith Gbenoudon Satoguina; Clemens H. Cocken; Alan W. Thomas; Jean Langhorne; Ambaliou Sanni (European Scientific Journal, ESJ, 2017)
The present study aimed at measuring the capacity of naturally occurring antibodies to bind Pf83/AMA-1 and MSP-1/19 antigens, two malaria vaccine candidates, in an immunoassay. According to the fact that antibody prevalence reflects endemicity of malaria, we further aimed at using the results obtained here as baseline data set to follow up and evaluate the expected decline in endemicity in 2016, 8 years after the change in drug policy in Benin. Therefore, individuals, 2 – 19 and above 20 years old, living in Awansori, a malaria holoendemic area in the suburb of Cotonou, Benin were bled during the dry and raining seasons of the years 1994/1995. Antibody responses were measured using direct, indirect and competition ELISA. We found a very high prevalence of antibody responses (89 to 96%) in the studied population. The results indicate for Pf83/AMA-1, that naturally occurring antibodies bind to protective epitopes in a competition ELISA with a parasite inhibiting monoclonal antibody. The data and samples analysed here were collected during the rainy season 1994 and the following dry season 1994/1995.